Wacana Baru Islam-Jawa - Burhanudin, Jajat (Studia Islamika, 1998)
This paper is a review of the book M.C. Ricklefs,The Seen and Unseen Worlds in Java: History, Literature and Islam in the Court of Pakubuwana II 1726-1749, (Honolulu: Asian Studies Association of Australian in association with Allen & Unwin and University of Hawaii Press, 1998).As for as the Indonesian studies are concerned,Â  Java has become the most various points of view, concerning the javanese society and culture. The book by M.C Ricklefs, which is under discussion, can be said to have specific importance.DOI:Â 10.15408/sdi.v5i2.757